PENGARUH MULTIMEDIA INTERAKTIF TERHADAP MOTIVASI BELAJAR DI SMPN 37 KOTA MAKASSAR - Khatimah. S, Husnul; Bunyamin, Andi; Mustamin; Ahmad; Syahrul, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the use of interactive multimedia on the learning motivation of eighth-grade students in Islamic Religious Education subjects at SMP Negeri 37 Makassar. This study is motivated by the low learning motivation of students characterized by a lack of attention, interest, and activeness in the learning process. Therefore, innovation in learning is needed, one of which is through the use of interactive multimedia which is expected to be able to increase student learning motivation. The population in this study amounted to 225 eighth-grade students, with a sample determined using certain techniques to obtain a representative number of respondents. This study uses a quantitative approach with the ex post facto method. The data collection technique was carried out through questionnaires, while data analysis used multiple linear regression to determine the effect of independent variables on the dependent variable. The results showed that the use of interactive multimedia has a positive influence on student learning motivation. This can be seen from the increase in the average value of learning motivation from 65.20 to 78.45, with a percentage increase of 20.32%. In addition, the results of the regression analysis showed a coefficient value of β = 0.62, which indicates a positive relationship between interactive multimedia and learning motivation. The results of the hypothesis test also showed a significance value of 0.000 < 0.05, so the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Thus, it can be concluded that the use of interactive multimedia has a significant effect on the learning motivation of eighth grade students in Islamic Religious Education at SMP Negeri 37 Makassar.